Evaluation of the Implementation of the Covid-19 Management Program in Takalar Regency - Arfayanti Eka Pertiwi Basri, Muhammad Alwy Arifin, Darmawansyah, Amran Razak4, Syamsuar, Stang (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Takalar Regency is included in the red zone in the spread of Covid-19 with a total of 292 people who were confirmed positive for Covid-19 in November 2020. The government's efforts by implementing policies through various programs have been carried out. This study aims to evaluate the impact of the implementation of the COVID-19 prevention program in Takalar Regency. The type of research that will be used is qualitative research with a phenomenological approach through in-depth interviews and documentation. The informants consisted of 5 key informants and 2 additional informants. The validity of the data using triangulation of sources or informants. The results showed that at the input stage the availability of Human Resources was sufficient in terms of quantity, Human Resource Training for the 2020 COVID-19 Task Force was not maximally carried out, the availability of facilities in handling COVID-19 corpses was not sufficient, the existing budget was not sufficient. . At the stage of the process, it shows that human resources are placed according to their expertise, evaluation meetings are held once a month, cross-sectoral cooperation is closely intertwined, implementation guidelines are in accordance with regulations from the Ministry of Health, obstacles in data validation and data delays for positive confirmed cases, differences in data based on the request of the Village/Kelurahan Government and what is in the field as well as the circulation of hoax information in the community. At the output stage shows the fluctuating confirmation case. The program has not been optimal due to budget constraints and community culture. There is a need for increased education to the public regarding COVID-19.